2006
DOI: 10.1513/pats.200605-125sf
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Signaling Involved in Pulmonary Fibrosis and Emphysema

Abstract: The incidence of finding evidence of both emphysema and pulmonary fibrosis in the same patient has received increased attention. Several investigators have found on biopsy the presence of emphysema of the upper zones and diffuse parenchymal disease with fibrosis of the lower zones of the lung, especially associated with current or previous heavy smokers. Believed previously to be two different disease mechanisms, there are now data to implicate some common pathways of cell and molecular activation leading to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 55 publications
4
94
0
1
Order By: Relevance
“…Smad3 activation contributes to the induction of gene expression and the promotion of fibrosis. 24,29,30,74,75,77 Some data suggest that Smad3 can be activated by H 2 O 2 . 78,79 (v) It has been clearly demonstrated that the action of TGF-b is induced through the activation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smad3 activation contributes to the induction of gene expression and the promotion of fibrosis. 24,29,30,74,75,77 Some data suggest that Smad3 can be activated by H 2 O 2 . 78,79 (v) It has been clearly demonstrated that the action of TGF-b is induced through the activation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] Specifically, the Smad3 protein emerges as a pro-fibrotic member of the Smad protein family because its phosphorylation promotes the progression of fibrosis. 29,30 It has been reported that oxidative stress induces the EMT. Human epidermal keratinocytes exposed to H 2 O 2 showed protein expression that was consistent with the EMT, 31 and similar results were founded in renal tubular epithelial cells.…”
mentioning
confidence: 99%
“…Abnormal Smad signaling (i.e. overexpression of Smads 2/3) increases the production of collagens, which hence promotes deposition of extracellular matrix proteins (49). Once phosphorylated, Smads 2 and 3 that act downstream of the TGF-␤1 receptor form a complex with Co-Smad 4, which translocates to the nucleus to specifically regulate gene transcription (50).…”
Section: Silencing Of Cat B Impaired Smad Signaling Pathway Of Ccd19lumentioning
confidence: 99%
“…PAI-1 binds to fibrin and forms covalent complexes with t-PA or u-PA, eliminating plasminogen activation and fibrinolysis (Hertig and Rondeau 2004). Although some studies found that PAI-1 expression changed in emphysema models (Bonniaud et al 2004;Gauldie et al 2006), prior to the current report, the role of PAI-1 in the development of emphysema was not well understood.…”
Section: Discussionmentioning
confidence: 72%
“…It was found that Smad3 gene knockout mice showed age-related emphysema-like changes, and had a lower PAI-1 gene expression compared with wild-type mice (Bonniaud et al 2004). Overexpression of TGF-β in experimental rodent models led to upregulation of protease inhibitors, including PAI-1 (Gauldie et al 2006). However, a direct relationship between PAI-1 and change of lung structure with increasing age has not yet been found.…”
mentioning
confidence: 99%